Endothelial cell elongation and alignment in response to shear stress requires acetylation of microtubules - Moise, Katiannah; Arun, Keerthana M.; Pillai, Maalavika; Salvador, Jocelynda; Mehta, Aarya S.; Goyal, Yogesh; Iruela-Arispe, M. Luisa (Frontiers in Physiology, 2024)
The flow of blood imposes recurring and relentless physical forces on the vascular wall. The range of these physiological stressors includes distension, pressure, and shear stress. Cellular adaptations to these hemodynamic forces require remodeling of the cytoskeleton, with changes to actin, intermediate filaments, and microtubules. Here we used a range of imaging, pharmacological, and genetic perturbations to characterize alterations of microtubules in response to laminar shear stress. Our findings revealed that pharmacological suppression of microtubule dynamics blocks endothelial elongation and alignment, two typical responses to laminar shear stress. The findings demonstrate the essential contribution of the microtubular network to changes in cell shape driven by mechanical forces. Furthermore, we observed a flow-dependent increase in microtubule acetylation that occurred early in the process of cell elongation. Pharmacological manipulation of microtubule acetylation showed a direct and causational relationship between acetylation levels and endothelial elongation. Finally, genetic inactivation aTAT1, a microtubule acetylase, led to a significant loss of acetylation as well as inhibition of endothelial cell elongation in response to flow. In contrast, inactivation of HDAC6, a microtubule deacetylase resulted in robust microtubule acetylation with cells displaying faster kinetics of elongation and alignment. Taken together, our findings uncovered the critical contributions of HDAC6 and aTAT1, that through their roles in the regulation of microtubule acetylation, are key mediators of endothelial mechanotransduction.